A wearable electrofluidic actuation system. Issue 18 (9th August 2019) - Lin, Haisong; Hojaiji, Hannaneh; Lin, Shuyu; Yeung, Christopher; Zhao, Yichao; Wang, Bo; Malige, Meghana; Wang, Yibo; King, Kimber; Yu, Wenzhuo; Tan, Jiawei; Wang, Zhaoqing; et al.
Abstract : This work presents a wearable electrofluidic actuation system, which exploits the alternating current electrothermal (ACET) effects to engineer biofluid flow profiles on the body. Abstract : We report a wearable electrofluidic actuation system, which exploits the alternating current electrothermal (ACET) effects to engineer biofluid flow profiles on the body. The wearable ACET flow is induced with the aid of corrosion-resistant electrode configurations (fabricated on a flexible substrate) and custom-developed, wirelessly programmable high frequency (MHz) excitation circuitry. Various tunable flow profiles are demonstrated with the aid of the devised flexible ACET electrode configurations, where the induced profiles are in agreement with the ACET theory and simulation. The demonstrated capabilities rendered by the presented system create new degrees of freedom for implementing advanced bioanalytical operations for future lab-on-the-body platforms.